THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND FAMILY BUSINESS BACKGROUND ON THE INTENTION TO CONTINUE THE FAMILY BUSINESS AS THE NEXT GENERATION ON FAMILY BUSINESS STUDENTS IN CIPUTRA UNIVERSITY - Ortega Sevylla Tandra; Wiliam Santoso; Wendra Hartono; Charly Hongdiyanto; Gracia Ongkowijoyo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This Research is conducted to analyze the effect of entrepreneurship education and family business background on the intention to continue the family business as the next generation. This questionnaire was distributed to active students who are members of the Family Business Guild Classes 8.9 and 10 with a total of 169 respondents. This study uses Cluster Sampling where the sample will be divided by each batch. The data analysis method used in this research is Statistical Product and Service Solutions (SPSS) software with multiple linear regression analysis technique. The results of the analysis of this study stated that Entrepreneurship Education had no significant effect on the intention to continue the family business and the background of the family business had a positive relationship and had a significant effect on the intention to continue the family business. So it is stated that one of the factors that can influence students' interest in continuing their family business is the background of the family business. Where the child is able to establish good relations with the family so that work is not forced.